Inter-industrial relations and sectoral employment development in German regions - Julia Kowalewski (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
This paper aims to find evidence for the positive impact of cluster structures on employment development in Germany. It develops a new way of measuring the co-location of suppliers and buyers of intermediate goods in a region as well as the importance for the employment development in individual industries. The findings indicate that co-location of inter-connected industries did have a positive effect on employment growth in 16 out of 56 industries between 1998 and 2007 supporting the assumption that agglomeration advantages tend to occur within regional clusters rather than within single industries. However, for the majority of industries such advantages cannot be identified.
Keywords: R12; R15; J49; 330; input-output; shift-share; regional cluster; employment development; Regionales Cluster; Interindustrielle Verflechtung; Beschäftigungseffekt; Regionale Entwicklung; Shift-Share-Analyse; Schätzung; Deutschland